Factors impacting test-based management of suspected malaria among caregivers of febrile children and private medicine retailers within rural communities of Fanteakwa North District, Ghana - Olajoju Temidayo Soniran; Benjamin Abuaku; Abraham Anang; Patricia Opoku-Afriyie; Collins Ahorlu (BMC, 2021)
Abstract Background Prompt diagnosis and treatment prevents a mild case of malaria from developing into severe disease and death. Unfortunately, parasitological testing of febrile children is greater in the public and formal private sector than in the informal private sector in sub-Saharan Africa. Methods A mixed method study was carried out to determine factors limiting test-based management of suspected malaria cases among caregivers of febrile children and Over-the-Counter medicine sellers (OTCMS) in eight rural communities in Ghana. Structured questionnaires were used to interview 254 adult caregivers. Fourteen in-depth interviews were conducted with OTCMS. The interviews were audio-recorded, transcribed verbatim, and analysed thematically. Results The most frequently sought health providers by caregivers of febrile children in descending order were Community Health-Based Planning Services (CHPS) compounds; drug vendors; and OTCMS. Malaria parasitological testing rate of febrile children was highest (94.9%) at the CHPS compound and lowest (10.5%) at the OTCMS shops. Proportion of febrile children not subjected to malaria blood test is 28.3%. Among caregivers who did not ask for malaria blood test, 15.2% reported that healthcare provider did not offer a malaria blood test; 21.7% were financially handicapped to visit the Health Centre; and 63% lacked knowledge of malaria blood test and where to get it. From OTCMS point of view, clients' inability to pay for malaria blood test, community perception that OTCMS are unqualified to perform malaria blood test, financial loss when unused RDT kits expires, clients' demand for half dose of ACT, and activities of drug peddlers are factors limiting adherence to WHO recommended policy on testing before treating uncomplicated malaria cases. Conclusion The study results suggest the need to implement community friendly interventions aimed at improving test-based management of suspected malaria in febrile children. These may include educating caregivers and community members on the need to test and confirm malaria in febrile children before treating them, and supply of subsidized RDT kits to OTCMS and re-training them to provide testing services to their clients. Further studies pertaining to influence of gender roles on healthcare seeking attitude for febrile children is also suggested.